CORRELATION BETWEEN QUALITY HUMAN RESOURCE MANAGEMENT IN THE CAREER DEVELOPMENT OF EDUCATORS AND SCHOOL ACCREDITATION - Maulida; Agus Salim Salabi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Human resource (HR) management in education is a strategic element in ensuring sustainable school quality, particularly through planned and systematic career development of educators. HR management practices in many educational institutions still tend to be administrative and have not been fully integrated with efforts to improve school quality and meet accreditation standards. This study aims to explore the concept of quality-based HR management in educator career development and its relationship to achieving school accreditation through the perspective of national policy and academic literature. This study uses a narrative literature review approach by analyzing various primary and secondary literature sources, including scientific journal articles and relevant national education policy documents. The results of the study indicate that quality-based HR management which includes career planning, performance assessment, competency development, and ongoing professional development has a strong correlation with improving school quality and achieving accreditation. Effective implementation of human resource management encourages improved teacher performance, strengthens a culture of quality, and meets performance indicators in school accreditation instruments. The conclusion of this study confirms that quality-based human resource management in teacher career development is a strategic instrument for improving school accreditation. However, its success depends heavily on the principal's leadership capacity, consistency of internal policies, and support from a continuous professional development system.